(untitled) (Polish Yearbook of International Law, 2017)
This article discusses the classical question whether general principles of law form a separate source of international law. To this end it adopts the method of a posteriori analysis, examining the normative nature of various principles of law one by one. This analysis leads to the conclusion that only some principles have a normative nature, while others lack it.